Copper(I)/TEMPO Catalyzed Aerobic Oxidation of Primary Alcohols to Aldehydes with Ambient Air - Hoover, Jessica M. (2012)
This protocol describes a practical laboratory-scale method for aerobic oxidation of primary alcohols to aldehydes, using a chemoselective Cu(I)/TEMPO catalyst system. The catalyst is prepared in situ from commercially available reagents, and the reactions are performed in a common organic solvent (acetonitrile) with ambient air as the oxidant. Three different reaction conditions and three procedures for the isolation and purification of the aldehyde product are presented. The oxidations of eight different alcohols, described here, include representative examples of each reaction condition and purification method. Reaction times vary from 20 min to 24 h, depending on the alcohol, while the purification methods each take about 2 h. The total time necessary for the complete protocol ranges from 3 – 26 h.